Increased Posterior Insula-Sensorimotor Connectivity Is Associated with Cognitive Function in Healthy Participants with Sleep Complaints - Liu, Chun-Hong; Liu, Cun-Zhi; Zhu, Xue-Qi; Fang, Ji-Liang; Lu, Shun-Li; Tang, Li-Rong; Wang, Chuan-Yue; Liu, Qing-Quan (Frontiers in Human Neuroscience, 2018)
Insomnia is characterized by sensory hypersensitivity and cognitive impairments. Recent work in insomnia addressed that the insula is a central brain region involved in both bottom-up gating of sensory information and top-down cognitive control. However, the specific relationships between insular subregions connectivity and emotional as well as cognitive function remains are not clear. In this study, resting-state functional magnetic resonance imaging data were obtained from 25 healthy participants with sleep complaints (HPS) and 25 age, gender, and educational level matched healthy participants without insomnia complaints (HP). We performed insular subregion (ventral anterior, dorsal anterior, and posterior) functional connectivity to analyze the images. Cognitive function was accessed by a series of validated test procedures, e.g., the Wisconsin Card Sorting Test (WCST), Continuous Performance Test (CPT), and Trail making Test (TMT). There was no significant difference between the two groups in the WCST, CPT, and TMT. However, we indeed discovered that the HPS group showed enhanced connectivity between the right posterior insula (R-PI) to the left postcentral gyrus (L-postCG) when compared to HP group. The random errors of WCST, sleep disturbance scores, and HAMA scores correlated with R-PI to the L-postCG connectivity in all healthy participants. Our results provide direct evidence that the PI synchronizing with sensorimotor areas for sensing homeostatic changes and suggest that alteration of the latter is a key related to executive dysfunction.